2011
DOI: 10.2135/cropsci2011.02.0085
|View full text |Cite
|
Sign up to set email alerts
|

Varying Planting Dates or Irrigation Regimes Alters Cottonseed Composition

Abstract: Despite continued utilization of cottonseed {Gossypium hirsutum L.), little information exists regarding the effect of production factors on cottonseed composition. The objective of this study was to determine how irrigation regime and planting date affect cottonseed composition. Six cotton cultivars were planted early (late April) and at a normal time (late IVlay) in a field near Stoneville, MS, from 2005 to 2008. Half of the plots were irrigated and half were cultivated dry. Seed from the 2006 through 2008 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…The amount of nitrogen applied to our field plot was 35, 42 and 12 lbs/acre in the years 2009, 2010 and 2011, respectively. Pettigrew and Dowd () observed that frequent irrigation of cotton fields resulted in increased oil content and decreased protein content in the seed. Due to scant rainfall, our field was irrigated frequently in 2009, and even more in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of nitrogen applied to our field plot was 35, 42 and 12 lbs/acre in the years 2009, 2010 and 2011, respectively. Pettigrew and Dowd () observed that frequent irrigation of cotton fields resulted in increased oil content and decreased protein content in the seed. Due to scant rainfall, our field was irrigated frequently in 2009, and even more in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The TMR samples collected during wk 4 of each period were also were analyzed for indigestible ADF (ADF remaining after 288 h of in situ incubation) by the method of Huhtanen et al (1994). The 8 samples each of UCS, PCS, and PCSC were analyzed for total lipids according to AOAC International (1997; method 920.39; Dairyland Laboratories, Arcadia, WI) and for gossypol [total gossypol, (+)-gossypol, and (−)-gossypol] by methods based on AOCS Recommended Practice Ba 8a-99 (AOCS, 1998) as modified by Pettigrew and Dowd (2011). Frozen composites of alfalfa and corn silages were thawed and analyzed for NPN (Muck, 1987;Leco FP-2000 N Analyzer).…”
Section: Cottonseed Supplementsmentioning
confidence: 99%
“…The production of cottonseed oil has reached the third position after rapeseed and soybean (USDA-ERS, 2013). Cottonseeds are rich in protein (17-27%), oil (12-30%), saturated fatty acids (∼29%) and unsaturated fatty acids (∼70%) (Dowd et al, 2010;Pettigrew and Dowd, 2011). Various environmental and management practices influence the cottonseed composition despite genetic control (Pettigrew and Dowd, 2011;Bellaloui et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cottonseeds are rich in protein (17-27%), oil (12-30%), saturated fatty acids (∼29%) and unsaturated fatty acids (∼70%) (Dowd et al, 2010;Pettigrew and Dowd, 2011). Various environmental and management practices influence the cottonseed composition despite genetic control (Pettigrew and Dowd, 2011;Bellaloui et al, 2015). Thus, a better management of crops and environmental factors is essential to maintain and ensure high productivity and nutritional quality of cottonseeds.…”
Section: Introductionmentioning
confidence: 99%